2007
DOI: 10.1099/mic.0.2006/003327-0
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization and ecological roles of a novel exopolysaccharide from the deep-sea psychrotolerant bacterium Pseudoalteromonas sp. SM9913

Abstract: Pseudoalteromonas sp. SM9913 is a psychrotolerant bacterium isolated from deep-sea sediment. The structural characterization and ecological roles of the exopolysaccharide (EPS) secreted by this strain were studied in this work. The yield of the EPS increased as the culture temperature decreased in the range 30-10 6C, and it reached 5.25 g l "1 (dry weight) under optimal growth conditions (15 6C, 52 h). EPS fraction was purified and its structure was identified by the combination of NMR spectra, high-resolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 113 publications
(65 citation statements)
references
References 26 publications
3
62
0
Order By: Relevance
“…SM9913 Q-L Qin et al showed that SM9913 can produce large amounts of highly acetylated EPS (Qin et al, 2007a). These EPS can protect the cold-adapted protease MCP-01 produced by SM9913 from autolysis and can bind many metal ions because of their net negative charge and acidic properties (Qin et al, 2007a).…”
Section: Sensitivity To Reactive Oxygen Species (Ros)mentioning
confidence: 99%
See 4 more Smart Citations
“…SM9913 Q-L Qin et al showed that SM9913 can produce large amounts of highly acetylated EPS (Qin et al, 2007a). These EPS can protect the cold-adapted protease MCP-01 produced by SM9913 from autolysis and can bind many metal ions because of their net negative charge and acidic properties (Qin et al, 2007a).…”
Section: Sensitivity To Reactive Oxygen Species (Ros)mentioning
confidence: 99%
“…SM9913 Q-L Qin et al showed that SM9913 can produce large amounts of highly acetylated EPS (Qin et al, 2007a). These EPS can protect the cold-adapted protease MCP-01 produced by SM9913 from autolysis and can bind many metal ions because of their net negative charge and acidic properties (Qin et al, 2007a). Some deepsea bacteria with sequenced genomes, such as Idiomarina loihiensis (Hou et al, 2004) and A. macleodii 'deep ecotype' (Ivars-Martinez et al, 2008), have EPS biosynthesis genes, showing that the production of EPS may be a common strategy that deep-sea bacteria adopt to endure extreme conditions.…”
Section: Sensitivity To Reactive Oxygen Species (Ros)mentioning
confidence: 99%
See 3 more Smart Citations